2016
DOI: 10.1016/j.rmed.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

School environmental factors are predictive for exercise-induced symptoms in children

Abstract: This study showed an effect of cat allergen and environmental factors (humidity, air pressure) on the appearance of exercise related cough/bronchoconstriction during activity class in a natural environment at school in a large urban population of schoolchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Table shows the results of the subgroup analyses for the prevalence of EIB in general population of children and adolescents. Seven studies with sample size less than 400 showed a pooled mean prevalence of 15% (95% CI: 11‐19%), compared with 9% (95% CI: 7‐10%) in 12 studies with sample size between 400 and 1000, and 8% (95% CI: 7‐9%) in 14 studies with sample size greater than 1000 ( P < 0.001 for heterogeneity between subgroups). The global mean prevalence of EIB was 8% (95% CI 7‐9%) and 9% (95% CI 8‐10%) in the post hoc sensitivity analyses, excluding seven studies with sample size less than 400 and two studies with “poor” study quality, respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Table shows the results of the subgroup analyses for the prevalence of EIB in general population of children and adolescents. Seven studies with sample size less than 400 showed a pooled mean prevalence of 15% (95% CI: 11‐19%), compared with 9% (95% CI: 7‐10%) in 12 studies with sample size between 400 and 1000, and 8% (95% CI: 7‐9%) in 14 studies with sample size greater than 1000 ( P < 0.001 for heterogeneity between subgroups). The global mean prevalence of EIB was 8% (95% CI 7‐9%) and 9% (95% CI 8‐10%) in the post hoc sensitivity analyses, excluding seven studies with sample size less than 400 and two studies with “poor” study quality, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Table summarizes the characteristics of the 66 included studies. Thirty‐three studies investigated the prevalence of EIB in general population of children and adolescents. Ten studies reported the prevalence of EIB in child and adolescent athletes, and 23 studies in children and adolescents with asthma.…”
Section: Resultsmentioning
confidence: 99%
“…We found 64% of pectus patients reported dyspnea on exertion, a finding almost identical to Kelly's 63% in a prospective observational study of 327 pectus patients 34 . Prior studies in adolescents report an overall prevalence of dyspnea with exertion ranging from 7% to 14% suggesting individuals with pectus experience greater dyspnea symptoms than would be expected in the general population 35,36 . In our study, among the those reporting dyspnea on exertion nearly three-quarters had normal CPET, and dyspnea was not associated with a reduced VO 2 by multivariable linear regression modeling.…”
Section: Discussionmentioning
confidence: 94%
“…In a study made with the aim to understand if school also could be a significant site of allergen exposure for children in terms of environmental factors, such as atmospheric conditions and the presence of allergens, both potentially predictive of exercise-induced symptoms during physical education, it was showed an effect of environmental factors, like humidity and barometric pressure, and environmental allergens, in particular it was observed of cat allergens, on the occurrence of the EIB and cough in schoolchildren (38). Atopy and upper airway diseases are also known to influence EIB.…”
Section: Atopy and Environmental Factorsmentioning
confidence: 99%